Analysis of Factors Affecting Reporting of Patient Safety Incident in Nurses - Wanda, Maria Yuventa; Nursalam, Nursalam; Wahyudi, Andri Setiya (Fundamental and Management Nursing Journal, 2020)
Introduction: Patient Safety Incident Report hereinafter referred to as incident reporting, is a system of documenting patient safety incident reports, analyzing and obtaining recommendations and solutions from the health care facility patient safety team. This study aims to analyze the factors of work experience, education, perceptions, attitudes, motivation, leadership towards reporting patient safety incidents to nurses in the inpatient room of Prof. Dr. W. Z. Johannes Kupang.Method: The design of this study was cross-sectional. The sample size of the study was 143 respondents who met the inclusion criteria. The dependent variable is the reporting of patient safety incidents, while the independent variables are work experience, education, perception, attitude, motivation,  leadership. Data were collected using a questionnaire and observation on nurses. Data were then analyzed using multiple logistic regression with a significant value < 0.05.Results:  The results show that there is a perception effect on patient safety incident reporting (p = 0.05) and leadership influence on patient safety incident reporting (p = 0.02).Conclusion: The concludes is that there is an influence of perception and leadership on reporting patient safety incidents. Further researchers are advised to research the effect of training on improving patient safety incident reporting.